(untitled) (Journal of the College of Education for Women, 2019)
The Maghreb Did not know modern problem more complex and dangerous than the problem of Western Sahara, which is the first obstacle in front of building Arab Maghreb, did not enter Post-independence governments in attrition mutual since liberation wars until today, as happened with this problem between Morocco and Algeria supporting the Polisario Front separatist and did not know the end after so, this research focused on the show dimensional geopolitical to this problem and reveal the role of regional and international behind its continuation and the latest developments after the revolutions Arab Spring and its impact on the problem and the end of UN mission new to the Sahara and results.